2019
DOI: 10.1016/j.cgh.2018.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Rate of Relapse and Effects of Steroid Maintenance Therapy in Patients With Autoimmune Pancreatitis: Systematic Review and Meta-analysis

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e64. Learning Objective-Upon completion of this activity, successful learners will be able to choose critically the exams that should be performed to diagnose autoimmune pancreatitis; recognize, diagnose, and describe possible other organ involvement in patients with IgG4-related autoimmune pancreatitis; and select the most appropriate test in the evaluation of suspected exocrine pancreatic insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 55 publications
0
36
0
2
Order By: Relevance
“…Regarding the employed therapeutic approach, surgery was performed in 11% of patients, in the majority for suspicion of pancreatic cancer, and most of the patients received steroids as initial treatment and as maintenance therapy, with a very high response rate, as previously documented. 31 Immunosuppressants and rituximab were used especially after relapses, even if rarely; only a small number of patients received azathioprine as first-line treatment, because other comorbidities contraindicated the use of steroids. Both immunosuppressive drugs and rituximab deserve to be further explored in randomized studies, in particular rituximab, which in a recent retrospective study on relapsing autoimmune pancreatitis looked very promising, having been shown to be more efficient than immunosuppressant drugs, and with better tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the employed therapeutic approach, surgery was performed in 11% of patients, in the majority for suspicion of pancreatic cancer, and most of the patients received steroids as initial treatment and as maintenance therapy, with a very high response rate, as previously documented. 31 Immunosuppressants and rituximab were used especially after relapses, even if rarely; only a small number of patients received azathioprine as first-line treatment, because other comorbidities contraindicated the use of steroids. Both immunosuppressive drugs and rituximab deserve to be further explored in randomized studies, in particular rituximab, which in a recent retrospective study on relapsing autoimmune pancreatitis looked very promising, having been shown to be more efficient than immunosuppressant drugs, and with better tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis on risk factors including 36 studies also demonstrates that type 1 AIP has a higher relapse rate (37.5% vs 15.9%; p < 0.01). 23 Tacelli et al highlight the controversial results between the different studies. Jaundice was the most common significant risk factor for AIP in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, relapse occurs in 24-52% of type 1 AIP cases [22,29,[72][73][74][79][80][81][136][137][138][139][140][141][142][143][144] and 0-27% of type 2 AIP cases [21,73,78] after cessation of corticosteroid treatment or dose tapering of corticosteroids. Identification of characteristics or risk factors for relapse is critical, as unnecessary steroid treatment in patients in whom recurrence is unlikely should be avoided.…”
Section: Recurrence Of Aip and Factors Associated With Recurrencementioning
confidence: 91%
“…To date, several factors for predicting AIP relapse have been reported. These include a high level of serum IgG4 [22,79]; extrapancreatic lesions [78,80,136,137], especially proximal bile duct stenosis [73,136,138]; retroperitoneal fibrosis [139]; dacryoadenitis/sialadenitis [140]; jaundice [141]; discontinuation of steroid therapy [138,142,143]; a small reduction in the level of serum sIgG4 3-4 months after steroid initiation [80,81]; and a low level of pancreatic shrinkage following steroid treatment [144]. Maintenance corticosteroid therapy, with or without steroid-sparing agents, is recommended for type 1 AIP patients with factors predictive of relapse, although the therapeutic period is unclear.…”
Section: Recurrence Of Aip and Factors Associated With Recurrencementioning
confidence: 99%